2003
DOI: 10.1021/bi027173g
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity of Each of the Three Steps of the Heme Oxygenase Reaction:  Hemin to meso-Hydroxyhemin, meso-Hydroxyhemin to Verdoheme, and Verdoheme to Biliverdin

Abstract: Heme oxygenase catalyzes the regiospecific oxidation of hemin to biliverdin IXalpha with concomitant liberation of CO and iron by three sequential monooxygenase reactions. The alpha-regioselectivity of heme oxygenase has been thought to result from the regioselective oxygenation of the heme alpha-meso position at the first step, which leads to the reaction pathway via meso-hydroxyheme IXalpha and verdoheme IXalpha intermediates. However, recent reports concerning heme oxygenase forming biliverdin isomers other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 41 publications
4
43
0
Order By: Relevance
“…DISCUSSION HmuO, like HO-1, yields only the ␣-isomer of biliverdin (12). Regioselectivity of HO catalysis is defined at the first oxygenation step (50), where the remote hydroperoxo oxygen attacks the porphyrin ␣-meso-carbon to form ␣-meso-hydroxyheme (6,25). Previous studies have suggested that regiospecific degradation of heme by HO activity is primarily under the steric control.…”
Section: Resultsmentioning
confidence: 99%
“…DISCUSSION HmuO, like HO-1, yields only the ␣-isomer of biliverdin (12). Regioselectivity of HO catalysis is defined at the first oxygenation step (50), where the remote hydroperoxo oxygen attacks the porphyrin ␣-meso-carbon to form ␣-meso-hydroxyheme (6,25). Previous studies have suggested that regiospecific degradation of heme by HO activity is primarily under the steric control.…”
Section: Resultsmentioning
confidence: 99%
“…Even the binding site of O 2 is still uncertain because resonance structures of verdoheme involving a change in iron redox state (Fig. 2) Oxygen activation on the verdoheme iron has been proposed, analogous to the first step of meso-hydroxylation of heme in its ␣-regiospecificity (20). ␣-Selectivity of the first step is a result of steric hindrance imposed by the distal helix that covers the ␤-, ␥-, and ␦-meso-carbons but not the ␣-meso-carbon (23).…”
mentioning
confidence: 99%
“…Other protective mechanisms (e.g., metal-binding proteins, HSPs and so on) are upregulated to help the cells cope with the collateral damage of the haemorrhage. The ability of many synthetic metalloporphyrins to act as potent inducers may be related (in part) to the fact that they tend to be poor substrates for haem oxygenases [72,73] and thus they cannot be readily metabolised and cleared. The relatively long tissue residence time of some metalloporphyrins may also be related to this property and may help explain the potent adaptive resistance effects of these complexes.…”
Section: Speculation As To the Basis For Organometallic-induced Adaptmentioning
confidence: 99%
“…Understanding why the metalloporphyrins ultimately fail and what might be done to prevent the loss of neuroprotection may be key to halting disease progression entirely. To the extent that metalloporphyrins are acting via an adaptive resistance mechanism, the dosing regimen may prove to be critical; for example, dosing to achieve the classic steady-state plasma level may not be the optimal approach, particularly considering that many of the porphyrins are largely unmetabolised [72,73] and that tissue residence times can be much greater than plasma residence [28]. Intermittent treatment with medium to high doses, continuous low dosing, dose escalation and combination with other agents are only a few of the strategies being examined to find a regimen that provides longer-term protection.…”
Section: Can Therapeutic Effects Be Extended?mentioning
confidence: 99%